Needs, status and future directions in palliative care for children with cancer: an insight into the Italian situation - Chelazzi, Cosimo; Marelli, Daniele; Mantovani, Paola; Franchi, Francesca; Vezzoli, Cesare (Frontiers in Oncology, 2025)
Pediatric palliative care (PPC) is an essential component of holistic care for children with cancer, addressing the physical, emotional, psychosocial and existential needs of children and their families. This narrative review explores the status, challenges, and future directions of PPC for children with cancer, specifically focusing on the Italian context. Despite advancements in legislation, such as Italy’s Law 38/2010, access to PPC remains uneven, particularly in underserved regions. Children with cancer experience a high symptom burden, including pain, fatigue, and dyspnea, which is often inadequately managed due to late referrals and misconceptions equating PPC with end-of-life care. Organizational barriers, such as limited trained personnel and inadequate service models are linked to delayed integration. Physician discomfort, family resistance, and uncertainty regarding referral timing also contribute to delayed referral. International studies highlight regional disparities. However, opportunities for improvement exist, including workforce development, targeted education, and public awareness campaigns. Models of care, such as home-based services, telemedicine, and floating clinics, demonstrate potential for addressing gaps and optimizing resource allocation. Data from Italian centers further emphasize the importance of early PPC integration to improve outcomes, reduce unnecessary intensive care interventions, and ensure a better quality of life. This review underscores the need for tailored, multidisciplinary PPC models, proactive screening tools, and sustained policy support to ensure equitable and comprehensive care for all children with cancer.